NIKAH SIRI DI PERSIMPANGAN AGAMA DAN NEGARA: SOLUSI ATAU MASALAH BARU? - Nissa, Reina Khoirun; Achdiani, Yani; Nastia, Gina Indah Permata (Cahaya Ilmu Bangsa, 2025)
Unregistered marriages, marriages that are legal according to religion but not registered with state institutions, raise various legal, social, and cultural issues in Indonesia. These marriages are often chosen for various reasons, such as certain legal prohibitions, or social burdens. However, not registering a marriage can have serious consequences, especially for women and children. This review discusses the impatcs of unregistered marriages from the perspectives of religion, the state, and society and suggest approaches to address the challenges that arise. The results of the study indicate that while unregistered marriages can be a solution in some circumstantes, the losses incurred tend to be greater, especially in terms of legal security and social welfare. Therefore, it is imperative to strengthen marriage registration at the individual and institutional levels. Nikah siri, pernikahan yang sah menurut agama tetapi tidak tercatat di lembaga negara, menimbulkan berbagai masalah hukum, sosial, dan budaya di Indonesia. Pernikahan ini sering dipilih karena berbagai alasan, seperti larangan hukuman tertentu, atau beban sosial. Namun, tidak dicatatkannya pernikahan secara resmi dapat berdampak serius, terutama bagi perempuan dan anak-anak. Pertimbangan ini membahas dapat perkawinan yang tidak dicatatkan dari sudut pandang agama, negara, dan masyarakat serta memberikan saran pendekatan untuk mengatasi tantangan yang muncul. Hasil dari penelitian menunjukkan bahwa meskipun perkawinan yang tidak dicatatkan dapat menjadi solusi dalam beberapa keadaan, kerugian yang ditimbulkan cenderung lebih besar, terutama dalam hal keamanan hukum dan kesejahteraan sosial. Oleh karena itu, sangat penting untuk memperkuat pencatatan pernikahan di tingkat perorangan dan kelembagaan.